Masseter-facial neurorrhaphy for facial palsy reanimation: What happens after masseter denervation? Histomorphometric and stomatognathic functional analysis. Issue 7 (July 2020) - Cassoni, Andrea; Catalano, Carlo; Di Giorgio, Danilo; Raponi, Ingrid; Di Brino, Martina; Perotti, Stefano; Valentini, Valentino
Abstract: The aim of the present study was to analyse the consequences of masseter muscle denervation. In facial palsy surgical treatment, the masseteric nerve constitutes an important nerve source for facial reanimation due to its anatomical position and large amount of available axons. Computed tomography and/or magnetic resonance imaging were performed in 30 control subjects, and three radiologists separately measured the longitudinal diameter (LD), anteroposterior diameter (APD), transverse diameter (TD), and skeletal muscle area (SMA) of the masseter muscles as reference values. Regarding the facial palsy group, from 2009 to 2018, 11 patients (4 men and 7 women) were selected on the following inclusion criteria: diagnosis of unilateral facial paralysis, minimum follow-up of 14 months, absence of temporomandibular dysfunction, presence of complete dentition (to minimise bias of stomatognathic evaluation), complete clinical and radiological records. The mean LD, APD, TD, and SMA values of the healthy and denervated masseter muscles were obtained and compared. Stomatognathic function was clinically examined through mean mouth opening (MMO) and Maximum Bite Force (MBF). Furthermore, facial symmetry analysis (FSA) was carried out using EMOTRICS Software. Reference values obtained were as follows: mean LD = 69 ± 5.9 mm (range: 59–85 mm); mean APD = 40.2 ± 3.3 mm (range: 34–48 mm); mean TD = 15.5 ± 3.1 mm (range: 11–26 mm); and mean SMA = 43.8 ± 13.5 mm 3 (range: 26–85.8 mm 3 ). No statistically significant difference was observed between the healthy facial palsy groups's masseter muscles and reference values. As the latter, in denervated masseter muscles, no statistically significant difference was observed for APD value in contrast to LD, TD and SMA that showed statistically significant difference in comparison with control population (p < 0.05, CI 95%). Moreover fibro-adipose degeneration was consistently observed, with its degree being directly proportional to the denervation time. MMO and MBF mean values were, respectively, 54.75 mm in men, 44.4 mm in women and 705N. None of the latter showed a statistically significant difference with respect to the control population and the parameters present in the literature, indicating that masseter-facial neurorrhaphy is a safe and effective procedure for facial reanimation with good functional and aesthetic outcomes.